Hemodynamic Parameters Predict In-stent Thrombosis After Multibranched Endovascular Repair of Complex Abdominal Aortic Aneurysms: A Retrospective Study of Branched Stent-Graft Thrombosis - Liu, Ming-Yuan; Jiao, Yang; Liu, Junjun; Zhang, Simeng; Li, Wei (Frontiers in Cardiovascular Medicine, 2021)
Background: Branch vessel occlusion is reported in endovascular repair of aortic pathology. This study aimed to evaluate the hemodynamic indicators associated with in-stent thrombosis (IST) of a branched stent-graft (BSG) after endovascular aortic repair (EVAR) of a complex abdominal aortic aneurysm. Methods: A retrospective evaluation was performed based on the computed tomography (CT) scans and clinical data of three patients who underwent multi-branched endovascular repair. Patient-specific 3-dimensional models were reconstructed, and hemodynamic analysis was performed for IST. Hemodynamics-related parameters including time-averaged wall shear stress (TAWSS), oscillatory shear stress index (OSI), and relative residence time (RRT) were compared among the individual patients. Results: The flow velocity, TAWSS, OSI, and RRT were radically changed in the area of the IST. In BSGs, IST tended to occur in the regions of hemodynamic alteration near the bends in the device, where a decreased flow velocity (<0.6 m/s) and TAWSS (<0.8 Pa) and an elevated OSI (>0.2) and RRT (>5 s) were consistently observed. Conclusions: Hemodynamic perturbations in BSGs cause a predisposition to IST, which can be predicted by a series of changes in the flow parameters. Early hemodynamic analysis might be useful for identifying and remediating IST after multibranched endovascular repair.